2018
DOI: 10.1246/bcsj.20180033
|View full text |Cite
|
Sign up to set email alerts
|

Radical Metalloids with N-Heterocyclic Carbene and Phenanthroline Ligands: Synthesis, Properties, and Cross-Coupling Reaction of [(Nitronyl Nitroxide)-2-ido]metal Complexes with Aryl Halides

Abstract: New radical metalloids, NN-AuSIMes and NN-Cu(bdmpphen), were prepared and their properties were investigated. They were applied to Pd(0)-mediated cross-coupling reactions with aryl halides (ArX) to produce 2-aryl (nitronyl nitroxide)s in moderate to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The two compounds have similar values of oxidation potential: E1/2 ox = −0.03 V for NN-Au-P t BuPh2 and E1/2 ox = −0.06 V for NN-Au-P t Bu2Ph (vs. the Fc/Fc + redox couple), which is comparable to that of NN-Au-PPh3 (E1/2 ox = −0.07 V). Overall, the organogold paramagnets have low oxidation potential as compared, for example, to that of NN-H (+0.38 V) [18]. This specific feature of the NN gold derivatives, as shown above, drastically affects the crystal packing of radicals.…”
Section: Electrochemical Properties Of Nn-au-p T Buph2 and Nn-au-p T mentioning
confidence: 90%
“…The two compounds have similar values of oxidation potential: E1/2 ox = −0.03 V for NN-Au-P t BuPh2 and E1/2 ox = −0.06 V for NN-Au-P t Bu2Ph (vs. the Fc/Fc + redox couple), which is comparable to that of NN-Au-PPh3 (E1/2 ox = −0.07 V). Overall, the organogold paramagnets have low oxidation potential as compared, for example, to that of NN-H (+0.38 V) [18]. This specific feature of the NN gold derivatives, as shown above, drastically affects the crystal packing of radicals.…”
Section: Electrochemical Properties Of Nn-au-p T Buph2 and Nn-au-p T mentioning
confidence: 90%
“…Recent progress in the chemistry of NN radicals has led to the direct introduction of the NN group to organic and organometallic platforms using a parent NN ( NN‐H ) as a synthetic unit, which can easily convert a nucleophilic radical anion by deprotonation at the C2‐position (Scheme 1). [8−14] To date, the properties of a series of organometallic NN radicals NN‐M−L [M: Hg II , [8] Pt II , [9] Pd II , [10] Au I , [11−13] Ag I , [12] Cu I ; [12,13] L: acetate (OAc), phosphine ligand (PR 3 ), 2,2′‐bipyridine ligand, and N ‐heterocyclic carbene ligand (NHC) as examples] have been investigated and their interesting redox [9,10,12] and electronic‐spin properties have been discovered [10,11] . We also found that NN‐Au‐L is an attractive cross‐coupling reagent for the introduction of an NN group in the reaction with aryl bromide or aryl iodide [11a] .…”
Section: Introductionmentioning
confidence: 99%
“…Direct introduction of a radical group in a molecular skeleton is an attractive strategy for creation of spin-based materials. The use of a nitronyl nitroxide radical 15 exemplifies this approach. However, to use trityl-based persistent hydrocarbon radicals in this strategy, a functional group would need to be introduced before generating the radical (pre-modification) for avoiding rapid decomposition, 16 and the post-modification of the persistent radicals is still limited.…”
mentioning
confidence: 99%